Growth Characteristics Layur Fish Lepturacanthus savala in Juata Waters, Tarakan, Indonesia - Agus Indarjo; Gazali Salim; Fahrizal Amir; Supriadi Supriadi; Permana Ari Soejarwo; Christine Dyta Nugraeni; Lukman Yudho Prakoso; Ambariyanto Ambariyanto; Muhammad Firdaus; Julian Ransangan (Marine Science Department Diponegoro University, 2020)
The city of Tarakan, Indonesia, benefits economically from abundant marine biological resources, one of which is the layur fish, known commercially as ribbonfish. The purpose of this study was to analyze the growth character of the layur fish (Lepturacanthus savala) obtained from the juata waters of Tarakan City. The method of this quantitative and descriptive study was to analyze the growth of layur fish Lepturacanthus savala in the Juata waters off the coast from the city of Tarakan. Body shape, length, weight, and ratio sex data were collected from sites selected by the purposive sampling method based on trawl fishing catch. Secondary data, collected from interviews of fishing personnel, included the number of catches using trawling gear and trawl fishing location. The length ranges of male from 20,4 to 54,0 cm with an average length of 37,2±16.8 cm (n = 255) and the length ranges of female from 20,5 to 68 cm with an average length of 44,25±23.75 cm (n = 275). The results showed that maximum length of male layur fish was smaller than the maximum length of female fish, which were 59.352 cm at 267 d and 72.638 cm at 315 d, respectively. The result shows a negative allometric growth pattern male and female layur fish was found to be the same and sex ratio of male to female has a ratio of 1,0: 1,8 with a percentage of males at 48.11% and females at 51.89%. The majority of male and female fish exhibited a thin body shape (51,4% of male and 52% of female).